Performance Comparison of Two Anaesthetic Facemasks - Ball, A. J.; Craig, J.; Green, R. J.; Richardson, D. J. (Anaesthesia and intensive care, 2007)
When considering anaesthetic masks, the quality of the mask-face seal is a key determinant of performance. This randomised crossover trial utilises expired oxygen concentration to compare the efficacy of two routinely used facemasks. Thirty subjects were randomised to breathe 100% oxygen via either a traditional reusable black rubber mask or the disposable Intersurgical Scented mask for three minutes. This was then repeated using the other mask. To compare the impact of mask design on the quality of the mask-face seal, it was necessary to minimise measures taken by the anaesthetist to correct for a poor seal. To achieve this, the anaesthetist was requested to hold the mask in a manner consistent with an airtight seal, but they were blinded to capnography and reservoir bag movement. Expired oxygen concentration was recorded at 15-second intervals. From the oxygen wash-in curves, the Intersurgical mask consistently outperformed the black rubber mask. At three minutes the Intersurgical mask performed better than the black rubber mask, with mean end-tidal oxygen concentrations of 86.9% vs. 81% respectively; P=0.008. These findings indicate that the soft cuff design of the intersurgical mask provided a better seal than the black rubber facemask.